1975
DOI: 10.1007/bf00584500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local cooling on sweating rate and cold sensation

Abstract: Subjects resting in a 39 degrees C environment were stimulated in different skin regions with a water cooled thermode. This local cooling produced decreases in sweating rate measured at the thigh and increases in magnitude estimates of the cold sensation. The are of cold stimulation varied from 111 cm2 to 384 cm2. Sensitivity coefficients of the changes in sweating rate and magnitude estimate were corrected for differences in size of the area of stimulation and change in skin temperature and were normalized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
2
2

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 8 publications
4
66
2
2
Order By: Relevance
“…Literature evidence on the reduction of sweat loss of the forehead by skin cooling 15) could explain our findings with regard to the decrease in sweat loss perception. Technically, we were not able to measure this parameter objectively, due to the intervention based on water pouring on the head and for safety reasons.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Literature evidence on the reduction of sweat loss of the forehead by skin cooling 15) could explain our findings with regard to the decrease in sweat loss perception. Technically, we were not able to measure this parameter objectively, due to the intervention based on water pouring on the head and for safety reasons.…”
Section: Discussionsupporting
confidence: 68%
“…Regarding head cooling 12,13) , the previous studies were performed in controlled conditions such as climatic chambers, or wearing cooling devices amidst performance comparisons 14) . In a study performed by Crawshaw et al in 1975, evidence indicated that the forehead would be one of the most sensitive places in the body to reduce sweat loss through skin cooling 15) . Thus, we hypothesized that the simultaneous washing of hands and head using 2 l of non-refrigerated water would be effective as a cooling method for workers.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution coefficients for sweating and vasodilation were obtained from Stolwijk (1971). The coefficients used in the UTCI-Fiala model to distribute the overall shivering and vasoconstriction responses were estimated from simulations of cold and extreme-cold exposures (Fiala et al 2001), while the skin sensitivity coefficients were obtained from Nadel et al (1973) and Crawshaw et al (1975).…”
Section: Sh and Csmentioning
confidence: 99%
“…body-segment cooling or heating b. thermal sensation scale c. thermal comfort scale The tests were designed to force local skin temperatures through a range of values. 19 body segments were tested 1 . The entire surface of a body segment was cooled or heated by using a sleeve of conditioned air that enclosed the segment (the head sleeve is shown in Figure 1a).…”
Section: S Localmentioning
confidence: 99%
“…The differences may depend on many factors: how the body's local thermoregulatory mechanisms respond to the body's overall thermal state, asymmetry in clothing insulation and environment conditions around the body, the rate of change in the body's skin and core temperatures, and on the thermal sensitivity of the different parts involved. Although the thermosensitivity of individual body parts has been investigated in the past (e.g., [1,2]), there have been no studies of how people integrate the sensations from all their body parts when judging their whole-body thermal sensation.…”
Section: Introductionmentioning
confidence: 99%